Defining Southeast Asia Through The Democratization of Technology: A Critical Discourse Analysis of Southeast Asian Representation in Tweets Regarding Raya and The Last Dragon - Irene Shendy Kharista (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
The development of technology has enabled the democratization of technology that helps minority groups to disseminate their own discourse outside the control of the dominant media. Through an analysis on a series of popular Twitter tweets made as responses towards the announcement of a Disney animated film Raya and the Last Dragon, this article explores how internet users who identify themselves as Southeast Asian respond to the representations of Southeast Asia produced by a multinational company. Using critical discourse analysis from van Dijk and representation theory, this article examines how popular tweets constructed a discourse on Southeast Asian representation by using their authority as 'Southeast Asian' to construct alternative representations in response to the representations created by popular media and how these reached other internet users. The results of the analysis show that while the representation discourse on the tweets was well received by internet users who identify themselves as 'Southeast Asian', some aspects used to construct the 'Southeast Asian' identity were disapproved of by some users who refused to associate themselves with the identity.